Promoting coffee-based agroforestry and women’s livelihood in Vietnam, resulting in 1Mt carbon sequestration potential - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
In northwest Vietnam, women's unions in nine provinces and ten local NGOsused "Training for Trainers” materials developed by CCAFS partners in the World Agroforestry (ICRAF) and CARE International to empower women and strengthen 65 Village Savings and Loan Associations in the production and marketing of coffee.